Analisis Yuridis dan Praktis Pemberhentian Presiden dalam Perspektif Hukum Tata Negara - Simandjuntak, Reynold; Sarumaha, Pia Bertha (Fakultas Ilmu Sosial dan Hukum, 2024)
The dismissal of the President in the Indonesian constitutional system is a complex and crucial issue, especially after the amendment to the 1945 Constitution of the Republic of Indonesia. This process involves legal and political aspects that can affect government stability. This research aims to analyze the mechanism for dismissing the President as regulated in the 1945 Constitution and the challenges faced in its implementation. The research method used is normative legal research, which examines the provisions in the 1945 Constitution and other statutory regulations. The research results show that the inconsistency between the political decisions of the People's Representative Council (DPR) and the legal decisions of the Constitutional Court (MK) is caused by normative phrases in the Constitution that provide freedom in interpretation. Therefore, better coordination is needed between the DPR, MPR, and MK to ensure a transparent and accountable process. Hopefully, this research can positively contribute to strengthening the constitutional system and law enforcement in Indonesia.